Investigation of zero crossing detection for first return stroke in negative cloud-to -ground lightning flash - Abdul Rahman, Ahmad Idil; Bahari, Muhammad Akmal; Baharudin, Zikri Abadi (Penerbit UTHM, 2019)
This paper aims to investigate the minimum threshold for zero crossing detection of the first return stroke in negative cloud-to-ground lightning flashes. The uncertainty for a minimum threshold to be set into a programmed software for an automatic zero crossing detection motivated the author to overcome the problem. The software was built-in MATLAB. The development of the software considered the important parameter of lightning strike from the preliminary breakdown stages until the first return strokes. A single station measurement was setup in Ayer Keroh, Malacca. 41 samples of duration of the zero crossing time were recorded by using Lecoy HDO4024 with 5 MS/s. The results showed that the minimum threshold for zero crossing detection was 40µs with 82.9% accuracy. In conclusion, the minimum threshold of zero crossing detection of the first return stroke in negative cloud-to-ground was determined